Non-slip and efficient antifouling ceramic tile and preparation method thereof
By preparing nanofouling-proof coatings on the surface of the tiles, traditional tiles are easily contaminated with stains, difficult to clean and insufficient wear resistance, achieving efficient pollution and wear resistance improvement, and improving the usage experience and safety of the tiles.
Patent Information
- Application Number
- CN202411807753.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2044-12-10
AI Technical Summary
Traditional ceramic tiles are prone to stains, difficult to clean, slippery and easy to cause safety accidents during use, and lack wear and weather resistance.
The nano-anti-fouling coating is prepared on the surface of the ceramic tile. The nano-solution consists of nano-silica, nano-zinc oxide, nano-alumina and other components. It forms a stable nano-solution through high-speed stirring, and is uniformly coated on the surface of the ceramic tile by dip coating, spray coating or spin coating. It is then processed in a drying box and a sintering furnace to ensure that the coating is closely integrated with the surface of the ceramic tile.
It significantly improves the anti-fouling performance and wear resistance of ceramic tiles, maintains the finish and aesthetics of the surface of ceramic tiles, reduces the amount of cleaners used and cleaning time, reduces maintenance costs and environmental burden, and improves the user's sense of security and satisfaction.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic tiles and preparation thereof, in particular to a ceramic tile with anti-slip and high-efficiency anti-fouling properties and a preparation method thereof. Background Art
[0002] With the continuous development of the construction and decoration materials industry, ceramic tiles, as a common decorative material, have been widely used in home decoration, commercial spaces, public facilities and other fields. However, there are some problems with traditional ceramic tiles during use, such as easy stains, difficult to clean, slippery and prone to safety accidents, which limit the application scope and user experience of ceramic tiles. At present, ceramic tile products on the market mainly improve the anti-fouling performance by increasing the hardness of the glaze and improving the glaze formula.
[0003] However, these methods can only reduce the adsorption of stains to a certain extent, and it is still difficult to achieve the ideal cleaning effect for oily stains and stubborn stains. At the same time, in order to improve the anti-slip performance of tiles, the method of increasing the surface roughness is usually adopted, but this will affect the aesthetics and cleanliness of the tiles. The wear resistance and weather resistance of traditional tiles also need to be improved. During long-term use, the surface of tiles is prone to wear and scratches, which affects their appearance and service life. Especially in outdoor or public places, tiles must also have good UV resistance and environmental aging resistance. Summary of the invention
[0004] The object of the present invention is to provide a non-slip and highly effective anti-fouling tile and a preparation method thereof in order to solve the above-mentioned problems.
[0005] The technical solution adopted by the present invention is as follows: a non-slip and highly effective anti-fouling ceramic tile, the surface of which is provided with a nano anti-fouling coating, the nano anti-fouling coating is made of a nano solution, and the nano solution comprises:
[0006] Nano silicon dioxide: 35-40 parts by weight;
[0007] Nano zinc oxide: 15-40 parts by weight;
[0008] Nano titanium dioxide: 15-20 parts by weight;
[0009] Polytetrafluoroethylene: 8-14 parts by weight;
[0010] Silane coupling agent: 3 to 8 parts by weight;
[0011] Nano-alumina: 7-15 parts by weight;
[0012] Organosilane modifier: 4 to 10 parts by weight;
[0013] Ultraviolet light absorber: 2 to 4 parts by weight;
[0014] Antibacterial agent: 2 to 4 parts by weight;
[0015] Wear-resistant filler: 4 to 8 parts by weight;
[0016] Deionized water: 20-30 parts by weight;
[0017] Dispersant: 2 to 5 parts by weight.
[0018] In a preferred embodiment, the preparation method comprises the following steps:
[0019] S1: Prepare raw materials and select high-quality tile substrates to ensure they have stable physical properties and good temperature resistance;
[0020] S2: Surface treatment, using physical or chemical methods to roughen the surface of the tile to increase its adhesion to the nano coating;
[0021] S3: Cleaning: Use deionized water to clean the surface of the tiles to ensure there is no dust, oil or impurities.
[0022] S4: preparing a nano solution, mixing nano silicon dioxide and nano zinc oxide antifouling materials in a certain proportion, adding deionized water, and fully dispersing them by high-speed stirring to form a stable nano solution;
[0023] S5: coating deposition, using dip coating, spray coating or spin coating method to evenly coat the nano solution on the tile surface;
[0024] S6: placing the ceramic tile coated with the nano solution in a drying oven, controlling the temperature at 60-100°C, and drying for 30-60 minutes;
[0025] S7: Put the dried ceramic tile into a sintering furnace, control the sintering temperature at 400-600°C, and the sintering time at 10-30 minutes, so that the nano coating is closely combined with the ceramic tile surface;
[0026] S8: Test the adhesion, wear resistance and anti-slip properties of the sintered tiles to ensure that they achieve the expected results;
[0027] S9: According to the performance test results, optimize and adjust the nano solution formula, coating thickness, and sintering process until the requirements are met;
[0028] S10: Apply the optimized preparation process to the production line for large-scale production;
[0029] S11: Sampling inspection is carried out on the produced tiles to ensure that each batch of products has anti-slip and high-efficiency anti-fouling properties; they can be put on the market only after they pass the inspection, after which the entire anti-slip and high-efficiency anti-fouling tile preparation process is completed.
[0030] In a preferred embodiment, in step S1, when selecting the ceramic tile substrate, its physical properties should be stable. The specific parameters include: density of 2.0-2.5 g / cm 3 , water absorption rate is less than 0.5%, and flexural strength is greater than 40MPa; at the same time, the substrate should have good temperature resistance and be able to withstand the highest temperature during sintering, which is not less than 650℃.
[0031] In a preferred embodiment, in step S2, the surface of the tile is roughened by sandblasting or acid etching; when sandblasting, quartz sand is used as an abrasive and the pressure is controlled at 0.4-0.6 MPa; when acid etching, diluted hydrochloric acid or sulfuric acid is used with a concentration of 5% to 10% and a treatment time of 5 to 10 minutes to form an appropriate roughness and increase the adhesion between the coating and the substrate;
[0032] In step S3, when cleaning the surface of the tile, deionized water is used, the water temperature is controlled at 20-30° C., and the cleaning time is not less than 5 minutes; in addition, ultrasonic cleaning equipment can be used to assist in cleaning to ensure that oil stains, dust and impurities are completely removed.
[0033] In a preferred embodiment, in step S4, the specific preparation method of the nano solution includes:
[0034] Mix deionized water and dispersant and stir evenly;
[0035] Gradually add nano silicon dioxide, nano zinc oxide, nano titanium dioxide, polytetrafluoroethylene, nano aluminum oxide, and wear-resistant filler, and continue stirring;
[0036] Add the organosilane modifier, UV absorber, and antimicrobial agent and continue stirring to ensure uniform dispersion;
[0037] Finally, add the silane coupling agent and stir thoroughly until a uniform and stable nano solution is formed.
[0038] In a preferred embodiment, in step S5, when the spraying method is adopted, the distance between the spray gun and the tile surface should be maintained at 20-30 cm, and the spraying pressure is 0.2-0.4 MPa; during spin coating, the rotation speed is controlled at 500-1000 rpm, and the spin coating time is 30 to 60 seconds to ensure that the nano solution is evenly coated on the tile surface.
[0039] In a preferred embodiment, in step S6, the ceramic tile coated with the nano solution is placed in a drying oven, the temperature is set to 80° C., and the drying time is 45 minutes; during the drying process, air circulation in the drying oven should be maintained to avoid local overheating.
[0040] In a preferred embodiment, in step S7, the dried ceramic tile is placed in a sintering furnace, the sintering temperature is set to 500°C, and the sintering time is 20 minutes; the heating rate is controlled at 5-10°C / min to ensure that the nano coating is tightly bonded to the ceramic tile surface;
[0041] In step S8, the sintered tiles are subjected to performance tests, including adhesion test (using the tape method, no falling off is qualified), wear resistance test (using a wear tester, the wear amount is less than 0.02g / 1000 times is qualified) and anti-slip test (using a friction coefficient tester, the friction coefficient is greater than 0.5 is qualified.
[0042] In a preferred embodiment, in step S9, the nano solution formula is adjusted according to the performance test results, such as increasing the nano alumina content to improve wear resistance, or adjusting the sintering temperature and time to improve the bonding strength between the coating and the substrate; the optimization process may require multiple experiments until all performance indicators meet the expected requirements;
[0043] In step S10, the temperature, pressure and rotation speed parameters in the production process are ensured to be consistent with those in the experimental stage; at the same time, quality monitoring in the production process is strengthened to ensure stable product quality.
[0044] In a preferred embodiment, in step S11, the produced tiles are sampled and inspected, and the sampling ratio is 1% of each batch; the inspection items include adhesion, wear resistance, and anti-slip properties, ensuring that each batch of products has anti-slip and high-efficiency anti-fouling properties; if the inspection is qualified, the product can be put on the market; if it is unqualified, the cause must be traced and rectification must be carried out until it is qualified.
[0045] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0046] 1. In the present invention, the anti-fouling performance of the ceramic tile is significantly improved by preparing a nano coating on the surface of the ceramic tile. The components such as silicon dioxide and zinc oxide in the nano coating can effectively reduce the adsorption of stains, making the surface of the ceramic tile easy to clean and keeping it bright and clean even during long-term use. Secondly, the addition of nano-alumina and wear-resistant fillers greatly enhances the wear resistance and scratch resistance of the coating, so that the ceramic tile can still maintain a good appearance and service life when subjected to daily wear. In addition, the addition of organosilane modifiers and ultraviolet absorbers not only improves the water resistance and weather resistance of the coating, but also extends the service life of the coating and reduces the impact of environmental factors on the performance of the coating.
[0047] 2. In the present invention, the nano coating not only provides functional protection, but also can maintain the original color and texture of the tile, and can even increase a certain degree of gloss, making the surface of the tile more beautiful and improving the decorative effect. Due to the anti-fouling properties of the coating, the tile is not easily stained in daily use, and even if there are stains, it is easier to clean, which greatly reduces the amount of detergent used and the time of cleaning work, and reduces maintenance costs. The use of nano coating reduces the demand for chemical detergents, thereby reducing the burden on the environment. In addition, the materials and technologies used in the preparation process can be designed to have less impact on the environment, in line with the concept of sustainable development. Tiles with anti-slip properties provide better safety performance during use, especially when used in slippery environments such as kitchens and bathrooms, which can effectively reduce the occurrence of slip accidents and improve the user's sense of security and satisfaction. The tiles produced by this preparation method can meet the needs of the high-end market due to their excellent performance and aesthetics, enhance the market competitiveness of the products, and bring better economic benefits to manufacturers. DETAILED DESCRIPTION
[0048] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0049] Embodiment 1:
[0050] A tile with anti-slip and high-efficiency anti-fouling properties, wherein the surface of the tile is provided with a nano anti-fouling coating, the nano anti-fouling coating is made of a nano solution, and the nano solution comprises:
[0051] Nano silicon dioxide: 35 parts by weight;
[0052] Nano zinc oxide: 15 parts by weight;
[0053] Nano titanium dioxide: 15 parts by weight;
[0054] Polytetrafluoroethylene: 8 parts by weight;
[0055] Silane coupling agent: 3 parts by weight;
[0056] Nano-alumina: 7 parts by weight;
[0057] Organosilane modifier: 4 parts by weight;
[0058] Ultraviolet light absorber: 2 parts by weight;
[0059] Antibacterial agent: 2 parts by weight;
[0060] Wear-resistant filler: 4 parts by weight;
[0061] Deionized water: 20 parts by weight;
[0062] Dispersant: 2 parts by weight.
[0063] The preparation method comprises the following steps:
[0064] S1: Prepare raw materials and select high-quality tile substrates to ensure they have stable physical properties and good temperature resistance.
[0065] S2: Surface treatment, using physical or chemical methods to roughen the surface of the tile to increase its adhesion to the nano coating.
[0066] S3: Cleaning: Use deionized water to clean the surface of the tiles to ensure there is no dust, oil or other impurities.
[0067] S4: preparing a nano solution, mixing antifouling materials such as nano silicon dioxide and nano zinc oxide in a certain proportion, adding deionized water, and fully dispersing them through high-speed stirring to form a stable nano solution.
[0068] S5: coating deposition, using methods such as dipping, spraying or spin coating to evenly coat the nano solution on the surface of the tile.
[0069] S6: Place the ceramic tile coated with the nano solution in a drying oven, control the temperature at 60-100° C., and dry for 30 to 60 minutes.
[0070] S7: Put the dried ceramic tile into a sintering furnace, control the sintering temperature at 400-600°C, and the sintering time at 10-30 minutes, so that the nano coating is closely combined with the ceramic tile surface.
[0071] S8: Test the adhesion, wear resistance, anti-slip properties and other performance of the sintered tiles to ensure that they achieve the expected results.
[0072] S9: Based on the performance test results, optimize and adjust the nano solution formula, coating thickness, sintering process, etc. until the requirements are met.
[0073] S10: Apply the optimized preparation process to the production line for large-scale production.
[0074] S11: Sampling inspection is carried out on the produced tiles to ensure that each batch of products has anti-slip and high-efficiency anti-fouling properties. Only qualified products can be put on the market, and then the entire anti-slip and high-efficiency anti-fouling tile preparation process can be completed.
[0075] In step S1, when selecting the ceramic tile substrate, its physical properties should be stable. The specific parameters include: density of 2.0-2.5g / cm 3, water absorption is less than 0.5%, and flexural strength is greater than 40MPa. At the same time, the substrate should have good temperature resistance and be able to withstand the highest temperature during sintering, which is not less than 650℃.
[0076] In step S2, the surface of the tile is roughened by sandblasting or acid etching. When sandblasting, quartz sand is used as an abrasive, and the pressure is controlled at 0.4-0.6MPa; when acid etching, diluted hydrochloric acid or sulfuric acid is used, with a concentration of 5% to 10%, and the treatment time is 5 to 10 minutes to form an appropriate roughness and increase the adhesion between the coating and the substrate;
[0077] In step S3, when cleaning the surface of the tile, deionized water is used, the water temperature is controlled at 20-30° C., and the cleaning time is not less than 5 minutes. In addition, ultrasonic cleaning equipment can be used to assist in cleaning to ensure that impurities such as oil, dust, etc. are completely removed.
[0078] In step S4, the specific preparation method of the nano solution includes:
[0079] Mix deionized water and dispersant and stir well.
[0080] Gradually add nano silicon dioxide, nano zinc oxide, nano titanium dioxide, polytetrafluoroethylene, nano alumina and wear-resistant filler and continue stirring.
[0081] Add the organosilane modifier, UV absorber and antimicrobial agent and continue stirring to ensure uniform dispersion.
[0082] Finally, add the silane coupling agent and stir thoroughly until a uniform and stable nano solution is formed.
[0083] In step S5, when the spraying method is adopted, the distance between the spray gun and the tile surface should be maintained at 20-30 cm, and the spraying pressure is 0.2-0.4 MPa. When spin coating, the rotation speed is controlled at 500-1000 rpm, and the spin coating time is 30-60 seconds to ensure that the nano solution is evenly coated on the tile surface.
[0084] In step S6, the ceramic tile coated with the nano solution is placed in a drying oven, the temperature is set to 80° C., and the drying time is 45 minutes. During the drying process, air circulation in the drying oven should be maintained to avoid local overheating.
[0085] In step S7, the dried ceramic tile is placed in a sintering furnace, the sintering temperature is set to 500°C, and the sintering time is 20 minutes. The heating rate is controlled at 5-10°C / min to ensure that the nano coating is tightly bonded to the ceramic tile surface;
[0086] In step S8, the sintered tiles are subjected to performance tests, including adhesion test (using the tape method, no falling off is qualified), wear resistance test (using a wear tester, the wear amount is less than 0.02g / 1000 times is qualified) and anti-slip test (using a friction coefficient tester, the friction coefficient is greater than 0.5 is qualified.
[0087] In step S9, according to the performance test results, the nano solution formula is adjusted, such as increasing the nano alumina content to improve wear resistance, or adjusting the sintering temperature and time to improve the bonding strength between the coating and the substrate. The optimization process may require multiple experiments until all performance indicators meet the expected requirements.
[0088] In step S10, the temperature, pressure, rotation speed and other parameters in the production process are ensured to be consistent with those in the experimental stage. At the same time, the quality monitoring in the production process is strengthened to ensure the stability of product quality.
[0089] In step S11, the produced tiles are sampled and inspected, with a sampling ratio of 1% of each batch. The inspection items include adhesion, wear resistance, anti-slip properties, etc., to ensure that each batch of products has anti-slip and high-efficiency anti-fouling properties. If the inspection is qualified, the product can be put on the market; if it is unqualified, the cause must be traced and rectification must be carried out until it is qualified.
[0090] In the present invention, the anti-fouling performance of the ceramic tile is significantly improved by preparing a nano coating on the surface of the ceramic tile. The components such as silicon dioxide and zinc oxide in the nano coating can effectively reduce the adsorption of stains, making the surface of the ceramic tile easy to clean and keeping it bright and clean even during long-term use. Secondly, the addition of nano-alumina and wear-resistant fillers greatly enhances the wear resistance and scratch resistance of the coating, so that the ceramic tile can still maintain a good appearance and service life when subjected to daily wear. In addition, the addition of organosilane modifiers and ultraviolet absorbers not only improves the water resistance and weather resistance of the coating, but also extends the service life of the coating and reduces the impact of environmental factors on the performance of the coating.
[0091] In the present invention, the nano coating not only provides functional protection, but also can maintain the original color and texture of the tile, and can even increase a certain degree of gloss, making the surface of the tile more beautiful and improving the decorative effect. Due to the anti-fouling properties of the coating, the tile is not easily stained in daily use, and even if there are stains, it is easier to clean, which greatly reduces the amount of detergent used and the time of cleaning work, and reduces maintenance costs. The use of nano coating reduces the demand for chemical detergents, thereby reducing the burden on the environment. In addition, the materials and technologies used in the preparation process can be designed to have less impact on the environment, in line with the concept of sustainable development. Tiles with anti-slip properties provide better safety performance during use, especially when used in slippery environments such as kitchens and bathrooms, which can effectively reduce the occurrence of slip accidents and improve the user's sense of security and satisfaction. The tiles produced by this preparation method can meet the needs of the high-end market due to their excellent performance and aesthetics, enhance the market competitiveness of the products, and bring better economic benefits to manufacturers.
[0092] Embodiment 2:
[0093] A tile with anti-slip and high-efficiency anti-fouling properties, wherein the surface of the tile is provided with a nano anti-fouling coating, the nano anti-fouling coating is made of a nano solution, and the nano solution comprises:
[0094] Nano silicon dioxide: 40 parts by weight;
[0095] Nano zinc oxide: 40 parts by weight;
[0096] Nano titanium dioxide: 20 parts by weight;
[0097] Polytetrafluoroethylene: 14 parts by weight;
[0098] Silane coupling agent: 8 parts by weight;
[0099] Nano-alumina: 15 parts by weight;
[0100] Organosilane modifier: 10 parts by weight;
[0101] Ultraviolet light absorber: 4 parts by weight;
[0102] Antibacterial agent: 4 parts by weight;
[0103] Wear-resistant filler: 8 parts by weight;
[0104] Deionized water: 30 parts by weight;
[0105] Dispersant: 5 parts by weight.
[0106] The preparation method comprises the following steps:
[0107] S1: Prepare raw materials and select high-quality tile substrates to ensure they have stable physical properties and good temperature resistance.
[0108] S2: Surface treatment, using physical or chemical methods to roughen the surface of the tile to increase its adhesion to the nano coating.
[0109] S3: Cleaning: Use deionized water to clean the surface of the tiles to ensure there is no dust, oil or other impurities.
[0110] S4: preparing a nano solution, mixing antifouling materials such as nano silicon dioxide and nano zinc oxide in a certain proportion, adding deionized water, and fully dispersing them through high-speed stirring to form a stable nano solution.
[0111] S5: coating deposition, using methods such as dipping, spraying or spin coating to evenly coat the nano solution on the surface of the tile.
[0112] S6: Place the ceramic tile coated with the nano solution in a drying oven, control the temperature at 60-100° C., and dry for 30 to 60 minutes.
[0113] S7: Put the dried ceramic tile into a sintering furnace, control the sintering temperature at 400-600°C, and the sintering time at 10-30 minutes, so that the nano coating is closely combined with the ceramic tile surface.
[0114] S8: Test the adhesion, wear resistance, anti-slip properties and other performance of the sintered tiles to ensure that they achieve the expected results.
[0115] S9: Based on the performance test results, optimize and adjust the nano solution formula, coating thickness, sintering process, etc. until the requirements are met.
[0116] S10: Apply the optimized preparation process to the production line for large-scale production.
[0117] S11: Sampling inspection is carried out on the produced tiles to ensure that each batch of products has anti-slip and high-efficiency anti-fouling properties. Only qualified products can be put on the market, and then the entire anti-slip and high-efficiency anti-fouling tile preparation process can be completed.
[0118] In step S1, when selecting the ceramic tile substrate, its physical properties should be stable. The specific parameters include: density of 2.0-2.5g / cm 3 , water absorption is less than 0.5%, and flexural strength is greater than 40MPa. At the same time, the substrate should have good temperature resistance and be able to withstand the highest temperature during sintering, which is not less than 650℃.
[0119] In step S2, the surface of the tile is roughened by sandblasting or acid etching. When sandblasting, quartz sand is used as an abrasive, and the pressure is controlled at 0.4-0.6MPa; when acid etching, diluted hydrochloric acid or sulfuric acid is used, with a concentration of 5% to 10%, and the treatment time is 5 to 10 minutes to form an appropriate roughness and increase the adhesion between the coating and the substrate;
[0120] In step S3, when cleaning the surface of the tile, deionized water is used, the water temperature is controlled at 20-30° C., and the cleaning time is not less than 5 minutes. In addition, ultrasonic cleaning equipment can be used to assist in cleaning to ensure that impurities such as oil, dust, etc. are completely removed.
[0121] In step S4, the specific preparation method of the nano solution includes:
[0122] Mix deionized water and dispersant and stir well.
[0123] Gradually add nano silicon dioxide, nano zinc oxide, nano titanium dioxide, polytetrafluoroethylene, nano alumina and wear-resistant filler and continue stirring.
[0124] Add the organosilane modifier, UV absorber and antimicrobial agent and continue stirring to ensure uniform dispersion.
[0125] Finally, add the silane coupling agent and stir thoroughly until a uniform and stable nano solution is formed.
[0126] In step S5, when the spraying method is adopted, the distance between the spray gun and the tile surface should be maintained at 20-30 cm, and the spraying pressure is 0.2-0.4 MPa. When spin coating, the rotation speed is controlled at 500-1000 rpm, and the spin coating time is 30-60 seconds to ensure that the nano solution is evenly coated on the tile surface.
[0127] In step S6, the ceramic tile coated with the nano solution is placed in a drying oven, the temperature is set to 80° C., and the drying time is 45 minutes. During the drying process, air circulation in the drying oven should be maintained to avoid local overheating.
[0128] In step S7, the dried ceramic tile is placed in a sintering furnace, the sintering temperature is set to 500°C, and the sintering time is 20 minutes. The heating rate is controlled at 5-10°C / min to ensure that the nano coating is tightly bonded to the ceramic tile surface;
[0129] In step S8, the sintered tiles are subjected to performance tests, including adhesion test (using the tape method, no falling off is qualified), wear resistance test (using a wear tester, the wear amount is less than 0.02g / 1000 times is qualified) and anti-slip test (using a friction coefficient tester, the friction coefficient is greater than 0.5 is qualified.
[0130] In step S9, according to the performance test results, the nano solution formula is adjusted, such as increasing the nano alumina content to improve wear resistance, or adjusting the sintering temperature and time to improve the bonding strength between the coating and the substrate. The optimization process may require multiple experiments until all performance indicators meet the expected requirements.
[0131] In step S10, the temperature, pressure, rotation speed and other parameters in the production process are ensured to be consistent with those in the experimental stage. At the same time, the quality monitoring in the production process is strengthened to ensure the stability of product quality.
[0132] In step S11, the produced tiles are sampled and inspected, with a sampling ratio of 1% of each batch. The inspection items include adhesion, wear resistance, anti-slip properties, etc., to ensure that each batch of products has anti-slip and high-efficiency anti-fouling properties. If the inspection is qualified, the product can be put on the market; if it is unqualified, the cause must be traced and rectification must be carried out until it is qualified.
[0133] In the present invention, the anti-fouling performance of the ceramic tile is significantly improved by preparing a nano coating on the surface of the ceramic tile. The components such as silicon dioxide and zinc oxide in the nano coating can effectively reduce the adsorption of stains, making the surface of the ceramic tile easy to clean and keeping it bright and clean even during long-term use. Secondly, the addition of nano-alumina and wear-resistant fillers greatly enhances the wear resistance and scratch resistance of the coating, so that the ceramic tile can still maintain a good appearance and service life when subjected to daily wear. In addition, the addition of organosilane modifiers and ultraviolet absorbers not only improves the water resistance and weather resistance of the coating, but also extends the service life of the coating and reduces the impact of environmental factors on the performance of the coating.
[0134] In the present invention, the nano coating not only provides functional protection, but also can maintain the original color and texture of the tile, and can even increase a certain degree of gloss, making the surface of the tile more beautiful and improving the decorative effect. Due to the anti-fouling properties of the coating, the tile is not easily stained in daily use, and even if there are stains, it is easier to clean, which greatly reduces the amount of detergent used and the time of cleaning work, and reduces maintenance costs. The use of nano coating reduces the demand for chemical detergents, thereby reducing the burden on the environment. In addition, the materials and technologies used in the preparation process can be designed to have less impact on the environment, in line with the concept of sustainable development. Tiles with anti-slip properties provide better safety performance during use, especially when used in slippery environments such as kitchens and bathrooms, which can effectively reduce the occurrence of slip accidents and improve the user's sense of security and satisfaction. The tiles produced by this preparation method can meet the needs of the high-end market due to their excellent performance and aesthetics, enhance the market competitiveness of the products, and bring better economic benefits to manufacturers.
[0135] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the term "comprise" or any other variant thereof is intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0136] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A tile with anti-slip and high-efficiency anti-fouling properties, characterized by: The surface of the ceramic tile is provided with a nano antifouling coating, which is made of a nano solution, and the nano solution includes: Nano silicon dioxide: 35-40 parts by weight; Nano zinc oxide: 15-40 parts by weight; Nano titanium dioxide: 15-20 parts by weight; Polytetrafluoroethylene: 8-14 parts by weight; Silane coupling agent: 3 to 8 parts by weight; Nano-alumina: 7-15 parts by weight; Organosilane modifier: 4 to 10 parts by weight; Ultraviolet light absorber: 2 to 4 parts by weight; Antibacterial agent: 2 to 4 parts by weight; Wear-resistant filler: 4 to 8 parts by weight; Deionized water: 20-30 parts by weight; Dispersant: 2 to 5 parts by weight.
2. The anti-slip and highly effective anti-fouling ceramic tile and its preparation method as claimed in claim 1, characterized in that: The preparation method comprises the following steps: S1: Prepare raw materials and select high-quality tile substrates to ensure they have stable physical properties and good temperature resistance; S2: Surface treatment, using physical or chemical methods to roughen the surface of the tile to increase its adhesion to the nano coating; S3: Cleaning: Use deionized water to clean the surface of the tiles to ensure there is no dust, oil or impurities. S4: preparing a nano solution, mixing nano silicon dioxide and nano zinc oxide antifouling materials in a certain proportion, adding deionized water, and fully dispersing them by high-speed stirring to form a stable nano solution; S5: coating deposition, using dip coating, spray coating or spin coating method to evenly coat the nano solution on the tile surface; S6: placing the ceramic tile coated with the nano solution in a drying oven, controlling the temperature at 60-100°C, and drying for 30-60 minutes; S7: Put the dried ceramic tile into a sintering furnace, control the sintering temperature at 400-600°C, and the sintering time at 10-30 minutes, so that the nano coating is closely combined with the ceramic tile surface; S8: Test the adhesion, wear resistance and anti-slip properties of the sintered tiles to ensure that they achieve the expected results; S9: According to the performance test results, optimize and adjust the nano solution formula, coating thickness, and sintering process until the requirements are met; S10: Apply the optimized preparation process to the production line for large-scale production; S11: Sampling inspection is carried out on the produced tiles to ensure that each batch of products has anti-slip and high-efficiency anti-fouling properties; they can be put on the market only after they pass the inspection, after which the entire anti-slip and high-efficiency anti-fouling tile preparation process is completed.
3. The anti-slip and highly effective anti-fouling ceramic tile and its preparation method as claimed in claim 1, characterized in that: In step S1, when selecting the ceramic tile substrate, its physical properties should be stable. The specific parameters include: density of 2.0-2.5g / cm 3 , water absorption rate is less than 0.5%, and flexural strength is greater than 40MPa; at the same time, the substrate should have good temperature resistance and be able to withstand the highest temperature during sintering, not less than 650℃.
4. The anti-slip and highly effective anti-fouling tile and its preparation method as claimed in claim 1, characterized in that: In the step S2, the surface of the tile is roughened by sandblasting or acid etching; when sandblasting, quartz sand is used as an abrasive and the pressure is controlled at 0.4-0.6 MPa; when acid etching, diluted hydrochloric acid or sulfuric acid is used with a concentration of 5% to 10% and a treatment time of 5 to 10 minutes to form an appropriate roughness and increase the adhesion between the coating and the substrate; In step S3, when cleaning the surface of the tile, deionized water is used, the water temperature is controlled at 20-30° C., and the cleaning time is not less than 5 minutes; in addition, ultrasonic cleaning equipment can be used to assist in cleaning to ensure that oil stains, dust and impurities are completely removed.
5. The anti-slip and highly effective anti-fouling tile and its preparation method as claimed in claim 1, characterized in that: In step S4, the specific preparation method of the nano solution includes: Mix deionized water and dispersant and stir evenly; Gradually add nano silicon dioxide, nano zinc oxide, nano titanium dioxide, polytetrafluoroethylene, nano aluminum oxide, and wear-resistant filler, and continue stirring; Add the organosilane modifier, UV absorber, and antimicrobial agent and continue stirring to ensure uniform dispersion; Finally, add the silane coupling agent and stir thoroughly until a uniform and stable nano solution is formed.
6. The anti-slip and highly effective anti-fouling tile and its preparation method as claimed in claim 1, characterized in that: In step S5, when the spraying method is adopted, the distance between the spray gun and the tile surface should be maintained at 20-30 cm, and the spraying pressure is 0.2-0.4 MPa; when spin coating, the rotation speed is controlled at 500-1000 rpm, and the spin coating time is 30-60 seconds to ensure that the nano solution is evenly coated on the tile surface.
7. The anti-slip and highly effective anti-fouling tile and its preparation method as claimed in claim 1, characterized in that: In step S6, the ceramic tile coated with the nano solution is placed in a drying oven, the temperature is set to 80° C., and the drying time is 45 minutes.
8. The anti-slip and highly effective anti-fouling tile and its preparation method as claimed in claim 1, characterized in that: In the step S7, the dried ceramic tiles are placed in a sintering furnace, the sintering temperature is set to 500°C, the sintering time is 20 minutes, and the heating rate is controlled at 5-10°C / min; In step S8, the sintered ceramic tiles are subjected to performance tests, including adhesion test, wear resistance test and anti-slip test (using a friction coefficient tester, and a friction coefficient greater than 0.5 is considered qualified).
9. The anti-slip and highly effective anti-fouling tile and its preparation method as claimed in claim 1, characterized in that: In step S9, the nano solution formula is adjusted according to the performance test results, such as increasing the nano alumina content to improve wear resistance, or adjusting the sintering temperature and time to improve the bonding strength between the coating and the substrate; The optimization process may require multiple experiments until all performance indicators meet the expected requirements; In step S10, the temperature, pressure and rotation speed parameters in the production process are ensured to be consistent with those in the experimental stage; at the same time, quality monitoring in the production process is strengthened to ensure stable product quality.
10. The anti-slip and highly effective anti-fouling tile and its preparation method as claimed in claim 1, characterized in that: In step S11, the produced tiles are sampled and inspected, with the sampling ratio being 1% of each batch; the inspection items include adhesion, wear resistance, and anti-slip properties, to ensure that each batch of products has anti-slip and high-efficiency anti-fouling properties; if the inspection is qualified, the product can be put on the market; if it is unqualified, the cause must be traced and rectification must be carried out until it is qualified.
Citation Information
Patent Citations
Superhydrophobic and wear-resistant glaze coating and preparation method thereof
CN110746114A
Flexible non-slip ceramic glaze, flexible non-slip ceramic tile and preparation method of flexible non-slip ceramic tile
CN111574246A
Tile-like wooden floor and preparation method thereof
CN112778896A
Super-antiskid multifunctional ceramic tile and preparation method thereof
CN117658614A
Unfired transparent composite functional coating for building curtain wall and preparation method of unfired transparent composite functional coating
CN117659838A
Cited By
Wax liquid for improving wear resistance of ceramic tile, preparation method and wear-resistant ceramic tile
CN121518018A